A primary amoebic meningoencephalitis case suspected to be infected by indoor swimming, China, 2024 - Li, Junfan; Feng, Songqi; Wang, Yao; Li, Chao; Li, Peng; Zhang, Lijie; Dai, Yingxue; Tan, Kaike; Wang, Liang (Frontiers in Medicine, 2025)
IntroductionNaegleria fowleri causes Primary Amoebic Meningoencephalitis (PAM), an unusual but fatal disease. Swimming in wild freshwater is commonly regarded as the primary cause of infection. In April, 2024, we discovered a case of PAM in a child, suspected to have contracted the infection through an uncommon route: indoor swimming. This article describes the field epidemiological investigation process, the reasoning behind the speculation of the infection origin, and recommendations for minimizing potential risks.MethodsFace-to-face visit was conducted with the guardian of the case. Field investigations were carried out at suspected venues of infection. Reasonable inferences were made by combining literature and investigation results.ResultsThe case manifested typical PAM symptoms, followed by death 7 days after onset. The suspected exposure period was between March 4 and April 3, associated with several instances of swimming in two indoor pools. A field investigation at N Aquatic Center revealed improper disinfection methods, substandard water quality, and a suitable environment for Naegleria fowleri.DiscussionN Aquatic Center is the most likely source of infection after synthesizing epidemiological history, field investigation, and laboratory results. Individuals can get infected even when swimming indoors if the water is not well managed. Inspecting, monitoring, and disinfecting pool water should be strengthened.